THE VIOLATION OF THE POLITENESS PRINCIPLE MAXIMS IN 300 MOVIE SUBTITLE - Rahman Wildana; Wisasongko Wisasongko; Agung Tri Wahyuningsih (Universitas Sebelas Maret, 2019)
This research focused on the violation of politeness maxims done by the characters in 300 movie. The violation has other meaning that mean different from the actual and expressed meaning. The objective of this research is to reveal the implied meaning that was uttered by the characters in 300 movie. Several theories are provided to help the researcher in revealing the related issue. The theories are pragmatics, politeness, politeness principle, and language and context. The type of this research is qualitative research because the data are in the form of sentences in a subtitle of 300 movie. The source of the data is taken from a website of icinema3satu.com and subscene.com. There are several steps to in processing the data in this research, first Classify all the utterances into each maxim using Leech’s politeness principle maxim approach (1983) to categorize the type of the principle maxim, and then Applying the language and context to find the reason and implied meaning of the violating maxims using Brown and Yule’s theory (1983). The researcher tries to analyze the data and find the types of maxims in 21 utterances uttered by 11 characters of 300 movie in using politeness principle theory